2014
DOI: 10.1542/peds.2013-2822
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perceptions and Subsequent Sexual Behaviors After HPV Vaccination in Adolescents

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Concerns have been raised that human papillomavirus (HPV) vaccination could lead to riskier behaviors in vaccinated adolescents, but it is unknown whether changes in risk perceptions after vaccination lead to riskier sexual behaviors.WHAT THIS STUDY ADDS: Risk perceptions following HPV vaccination were not associated with subsequent riskier sexual behaviors in sexually experienced and inexperienced young women. These data contribute to the growing evidence that HPV vaccination doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 33 publications
7
46
0
Order By: Relevance
“…More detailed results from the individual studies, including differences between vaccinated and unvaccinated women, can be found in previous articles. [16][17][18]20,21 HPV results were as follows: 69.0% were positive for at least one HPV type, 56.1% for at least one high-risk type, 21.2% for at least one 2-valent vaccine type (15.8% for HPV16 and 8.0% for HPV18), 27.2% for at least one 4-valent type, and 41.5% for at least one 9-valent vaccine type (Table 2). Among HPVinfected women, 81.4% were positive for at least one high-risk type, 30.7% for at least one 2-valent type (22.9% for HPV16 and 11.6% for HPV18), 39.5% for at least one 4-valent type, and 60.2% for at least one 9-valent type.…”
Section: Resultsmentioning
confidence: 99%
“…More detailed results from the individual studies, including differences between vaccinated and unvaccinated women, can be found in previous articles. [16][17][18]20,21 HPV results were as follows: 69.0% were positive for at least one HPV type, 56.1% for at least one high-risk type, 21.2% for at least one 2-valent vaccine type (15.8% for HPV16 and 8.0% for HPV18), 27.2% for at least one 4-valent type, and 41.5% for at least one 9-valent vaccine type (Table 2). Among HPVinfected women, 81.4% were positive for at least one high-risk type, 30.7% for at least one 2-valent type (22.9% for HPV16 and 11.6% for HPV18), 39.5% for at least one 4-valent type, and 60.2% for at least one 9-valent type.…”
Section: Resultsmentioning
confidence: 99%
“…These biased perceptions of vulnerability can result in increases in risky behavior (Mayhew et al, 2014). In contrast, perceptions of vulnerability to negative health outcomes and health-protective behaviors are usually heightened when people learn that similar others have experienced misfortune (Gerend, Aiken, West, & Erchull, 2004; Rothman et al, 1999; Weinstein & Klein, 1995).…”
Section: Social Comparison Theory Similarity and Risk Cognitionsmentioning
confidence: 99%
“…The factors include concern about sexual disinhibition following HPV vaccination of pre-teenage girls, although studies have shown that neither being offered HPV vaccine nor receiving it affected sexual behavior. [43][44][45] Availability of HPV9, which contains five additional strains, will protect against additional cancer-causing HPV strains, but initially may add confusion regarding HPV9 vaccination for adolescents who previously had received HPV2 or HPV4.…”
Section: Public Perceptionmentioning
confidence: 99%